Fear of COVID-19 predicts vaccination willingness 14 months later. (May 2022) - Mertens, Gaëtan; Lodder, Paul; Smeets, Tom; Duijndam, Stefanie
Abstract: Vaccines are an important tool for governments and health agencies to contain and curb the Coronavirus Disease-19 (COVID-19) pandemic. However, despite their effectiveness and safeness, a substantial portion of the population worldwide is hesitant to get vaccinated. In the current study, we examined whether fear of COVID-19 predicts vaccination willingness. In a longitudinal study ( N = 938), fear for COVID-19 was assessed in April 2020 and vaccination willingness was measured in June 2021. Approximately 11% of our sample indicated that they were not willing to get vaccinated. Results of a logistic regression showed that increased fear of COVID-19 predicts vaccination willingness 14 months later, even when controlling for several anxious personality traits, infection control perceptions, risks for loved ones, self-rated health, previous infection, media use, and demographic variables. These results show that fear of COVID-19 is a relevant construct to consider for predicting and possibly influencing vaccination willingness. Nonetheless, sensitivity and specificity of fear of COVID-19 to predict vaccination willingness were quite low and only became slightly better when fear of COVID-19 was measured concurrently. This indicates that other potential factors, such as perceived risks of the vaccines, probably also play a role in explaining vaccination willingness. Highlights: We examined whether fear of COVID-19 is a predictor of vaccination willingness. Fear of COVID-19 predicted vaccination willingness 14 months later. Several other predictors of vaccination willingness were also identified. Participants who did not want to vaccinate showed a pronounced decrease in fear. Prediction was imperfect, suggesting the role of additional factors.